Birth Control Use and Access Including Pharmacist-Prescribed Contraception Services during COVID-19 - Karli Pelaccio; David Bright; Heather Dillaway; Mary Beth O'Connell (MDPI AG, 2022)
The COVID-19 pandemic influenced health care with effects on contraception access emerging. The study objectives were to analyze pandemic impacts on birth control (BC) use and access; and evaluate perceptions of pharmacist-prescribed BC. A 50-item survey was distributed by 31 Michigan community pharmacies to women aged 18-45 over a three-month period. The survey link was also posted on two websites. 147 surveys were analyzed. Respondents were 29 ± 7.9 years old, primarily white (77%) and straight (81%). Fifty-eight percent of respondents used prescription BC, mostly to prevent pregnancy (84%) with oral pills (76%) being the most common formulation. Some BC users (25%) were worried about BC access and 27% had difficulty taking BC regularly. Half of the respondents (50%) would likely use pharmacist-prescribed BC if available, with advantages being more convenient than visiting a doctor's office (71%) and easier access (69%). The major concern about pharmacist-prescribed BC was women not receiving PAP smears and screenings (61%). Respondents reported high confidence (72%) in pharmacist-prescribed BC and believe it would help prevent unintended pregnancies (69%). Some respondents experienced altered BC use and access. Half of the respondents supported pharmacist-prescribed BC. Pharmacist-prescribed BC could help solve pandemic-related access problems.